ALGORITHMS FOR CONSTRUCTING THE DESCRIPTORS OF LOCAL IMAGE FEATURES BASED ON MULTIRING NONPARAMETRIC TRANSFORMATION - G. A. Butkin; I. A. Emelianov; A. V. Tuzikov (Informatika, 2017)
Application of nonparametric transformations for construction of local image features descriptors is considered. An approach based on scalable Bresenham circles for multiring nonparametric transformations is proposed. A problem of finding characteristic points (corners) in images is solved using two rings of small radius. Then, considering rings of greater radius a final decision is made concerning local features under investigation. Testing results of proposed local descriptors have demonstrated their competitiveness with known descriptors.